Paleoicnology of the Itararé Group in the State of Santa Catarina and Rio Negro City (PR), Brazil: a revision (Terr@ Plural, 2021)
The ichnofauna of the Itararé Group cropping out in Santa Catarina State (Southern Brazil) has been recorded since the work of Maury, in 1927, in the Southern city of Anitápolis. In the south of the State of Paraná, in the region of the city of Rio Negro, the first description of ichno assemblages was carried out in 2003 by Balistieri and collaborators, presenting a high density of arthropod traces. This work aims to identify and analyze the bibliographic production in paleoichnology of the Itararé Group throughout the State of Santa Catarina, and the Rio Negro region, seeking to understand the approaches adopted for the analysis of depositional successions. Sixteen studies with descriptions of the ichnofauna of six outcrops in five municipalities were found, analyzed, and discussed.
Keywords: glacial deposits; Mermia ichnofacies; Scoyenia ichnofacies; Cruziana; Diplichnites